Periodontal Microsurgical-Assisted Pouch and Tunnel Approach in Combination with Subepithelial Connective Tissue Graft for the Management of Class IIB and IIC Multiple Adjacent Gingival Recessions in Mandibular Anterior Segment - Salaria, Sanjeev Kumar (Contemp Clin Dent, 2018)
Gingival recession (GR) is an early and common clinical expression found in a majority of the population which increases with age. Different factors contribute to its etiology. It is a matter of concern for the patient which may be due to altered function and esthetics etc. Multiple conventional plastic surgical procedures are recommended for the management of GR depending on isolated or multiple GR. The present report described the plausible etiology of multiple adjacent GRs and classified it according to a new well-elaborated recession classification system proposed by Kumar and Masamatti, due to the limitation and applicability of most commonly used Miller's GR classification in the present clinical situation and its successful management through periodontal microsurgical-assisted pouch and tunnel approach in conjunction with subepithelial connective tissue grafting without any complication 6 months postoperatively.